Analisis Common Size dan Du Pont untuk Menilai Kinerja Keuangan PT Ciputra Development Tbk Periode 2020-2024 - Wita Dwi Handayani; Thoyibatun Nisa; Era Yudistira; Norta Idaman (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
This study aims to assess the financial performance of PT Ciputra Development Tbk for the 2020–2024 period using Common Size Analysis and the Du Pont System. This study applies quantitative descriptive analysis with secondary data in the form of financial reports published by the Indonesia Stock Exchange. Common Size Analysis is used to examine the structure and composition of financial reports, while the Du Pont System is used to analyze profitability through Net Profit Margin, Total Asset Turnover, and Return on Investment. The results show that the company's asset structure and capital tend to improve, indicated by an increase in the proportion of current assets and equity and a decrease in long-term liabilities. NPM shows quite good performance and is relatively stable above 20%, but TATO is still low, indicating that asset utilization is not optimal. As a result, ROI has decreased by an average of 4.54% and is still below the industry standard. Overall, the company's financial performance is quite stable, but operational efficiency and asset optimization need to be improved to be able to generate a maximum return on investment.